Bay or baylike regions of polycyclic aromatic hydrocarbons were potent inhibitors of Gap junctional intercellular communication. - Weis, L M (1998)
Many polycyclic aromatic hydrocarbons (PAHs) are known carcinogens, and a considerable amount of research has been devoted to predicting the tumor-initiating potential of PAHs based on chemical structure. However, there has been little research into the effects of PAHs on the epigenetic events of tumor promotion and no structural correlation has been made thereof. Gap junctional intercellular communication (GJIC) activity was used in this study as an epigenetic biomarker to determine the structure-activity relationships of twelve different PAHs. The PAHs used were naphthalene, 1-methylnaphthalene, 2-methylnaphthalene, anthracene, 1-methylanthracene, 2-methylanthracene, 9-methylanthracene, 9, 10-dimethylanthracene, phenanthrene, fluorene, 1-methylfluorene, and fluoranthene. Results showed that PAHs containing bay or baylike regions inhibited GJIC more than did the linear PAHs. The nonnaphthalene PAHs were not cytotoxic as determined by a vital dye uptake assay, but the naphthalene compounds were cytotoxic at the higher doses, indicating that the down regulation of GJIC by these naphthalenes could be a consequence of general membrane damage. Inhibition of GJIC by all the inhibitory PAHs was reversed when the cells were refreshed with PAH-free growth medium. Inhibition of GJIC occurred within 0.5-5 min and correlated with the aqueous solubility of the PAHs. The present study revealed that there are structural determinants of epigenetic toxicity as determined by GJIC activity.